2022
DOI: 10.1101/2022.07.27.501738
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative analysis of a large real-world cohort of small cell lung cancer identifies distinct genetic subtypes and insights into histological transformation

Abstract: Small cell lung cancer (SCLC) is a recalcitrant neuroendocrine carcinoma with dismal survival outcomes. A major barrier in the field has been the relative paucity of human tumors studied. Here we provide an integrated analysis of 3,600 real-world SCLC cases. This large cohort allowed us to identify new recurrent alterations and new genetic subtypes, including STK11-mutant tumors (1.7%) and TP53/RB1 wild-type tumors (5.5%), of which 12.7% were human papillomavirus-positive. In our cohort, gene amplifications on… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…Interestingly, such tumours usually retain oncogene driver mutations. In addition, similarly to de‐novo SCLC, these tumours gather RB1 mutations during tumor progression or present them as co‐alterations before treatment, evidence further supporting a major role of RB1 in promoting SCLC oncogenesis 102 …”
Section: Molecular Profile Of Lung Nensmentioning
confidence: 86%
See 1 more Smart Citation
“…Interestingly, such tumours usually retain oncogene driver mutations. In addition, similarly to de‐novo SCLC, these tumours gather RB1 mutations during tumor progression or present them as co‐alterations before treatment, evidence further supporting a major role of RB1 in promoting SCLC oncogenesis 102 …”
Section: Molecular Profile Of Lung Nensmentioning
confidence: 86%
“…In addition, similarly to de-novo SCLC, these tumours gather RB1 mutations during tumor progression or present them as co-alterations before treatment, evidence further supporting a major role of RB1 in promoting SCLC oncogenesis. 102 Recently, molecular studies have confirmed the existence of an overlapping class between NETs and NECs. This class, despite showing genetic alterations straddling between the two families of NENs, is counted as part of the NET spectrum, due to the presence of MEN1 mutation typical of NETs.…”
Section: Molecular Profile Of Lung Nensmentioning
confidence: 99%
“…In a recent preprint describing 3,600 SCLC tumor specimens analyzed for genomic alterations in ~300 cancer genes, ~1.5% and 0.7% of patients displayed alterations in TSC1 and TSC2 , respectively. 46 As we did not examine events such as silencing due to methylation or complex chromosomal rearrangements, it is possible that these percentages underestimate the prevalence of TSC1/TSC2 alteration in SCLC patients. Although only about 3%–4% of SCLC patients have TSC1 alterations according to our meta-analysis, a substantial fraction of SCLC patients possess PI3K-AKT-mTOR pathway alterations (e.g., 9%–10% patients with TSC2 alterations, 11%–12% with PTEN alterations).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms leading to lineage plasticity/histological transformation remain poorly understood at the current time. Similar to de novo SCLC (63,65), most cases of transformed SCLC harbor mutations in TP53 and RB1. Lineage plasticity is described in more detail by Drs.…”
Section: Chemotherapymentioning
confidence: 99%
“…In rare cases, histologic transformation from ALK-positive NSCLC to ALK-positive small cell lung cancer (SCLC) may be identified on post-progression biopsies ( 63 , 64 ). The molecular mechanisms leading to lineage plasticity/histological transformation remain poorly understood at the current time.…”
Section: Chemotherapymentioning
confidence: 99%